UJI FISIK DAN UJI HEDONIK SEDIAAN LIP CREAM EKSTRAK DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav) - Amanda, Larissa; Pratiwi, Pramita Yuli; Pradana, Riska Chandra (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Red Betel leaf (Piper crocatum Ruiz & Pav) has many benefits, one of the examples for antioxidant. Red Betel has not been widely used as a cosmetic preparation. This study was to know the result of physical test a lip cream with red betel leaf extract (Piper crocatum Ruiz & Pav) which has good physic and was liked by panelist. The use of red betel leaf extract in formula 1 was 0,9%, formula 2 was 1,2%, and formula 3 was 1,5% extract. Lip cream preparation tests produced from physical tests included organoleptic test, homogeneity, spreadability, adhesiveness, pH test, and hedonic test. The result of lip cream formulation indicated a homogeneous preparation, easy to spread with 5.2-5.4 cm, had a good adhesion with 10-20 second and owned pH of more than 4. The three formulas were by the standard requirement. In the hedonic test of texture, the most liked was formula 2 (83%), formula 3 was the most liked because of color (88%), and the aroma in formulas 1, 2, and 3 have the same aroma was liked by panelist (83%) The conclusion of the study was the result of a physical test of quality showed that each formulation accordance with a good lip cream standard.